Identity concerns drive belief: The impact of partisan identity on the belief and dissemination of true and false news. (January 2023) - Pereira, Andrea; Harris, Elizabeth; Van Bavel, Jay J.
We test three competing theoretical accounts invoked to explain the rise and spread of political (mis)information. We compare the ideological values hypothesis (people prefer news that bolster their values and worldviews); the confirmation bias hypothesis (people prefer news that fit their preexisting stereotypical knowledge); and the political identity hypothesis (people prefer news that allow them to believe positive things about political ingroup members and negative things about political outgroup members). In three experiments ( N = 1, 420), participants from the United States read news describing actions perpetrated by their political ingroup or outgroup. Consistent with the political identity hypothesis, Democrats and Republicans were both more likely to believe news about the value-upholding behavior of their ingroup or the value-undermining behavior of their outgroup. Belief was positively correlated with willingness to share on social media in all conditions, but Republicans were more likely to believe and want to share apolitical fake news.